GEOGRAFIA, CARTOGRAFIA E O BRASIL AFRICANO: ALGUMAS REPRESENTAÇÕES - Anjos, Rafael Sanzio Araújo (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2014)
Among the structural issues related to African culture in Brazil who continue deserving research and knowledge , highlights = is related to the geographical and historiographical aspects of our territorial formation , usually treated without due reference to mothers and " invisible " African ancestratlidades in Brazilian society . The paper rescues the main references of the geopolitics of diaspora Africa- America – Brazil and the current configuration of contemporary Afro-Brazilian population. The still dominant prejudiced social thinking and ignorance of the country's population , in relation to the African continent and its relations with Brazil , remain one of the structural barriers to real prospect of reduction of exclusion and invisibility secular , as well as the creation in the decision making sector, necessary for the effective implementation of the most articulate and satisfactory , especially in education and public policy outcomes geographical space condition.